DIGITAL BRANDING UNTUK MEMBANGUN CITRA LEMBAGA DI BALAI LATIHAN KERJA (BLK) SURABAYA - Afifah, Fitri’Atul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Objective: One strategy that can be implemented to strengthen the existence and build a positive image of the institution is through "Digital Branding". This study aims to analyze the strategies implemented by the Surabaya Vocational Training Center (BLK) in building the institution's image through digital branding in the era of digital transformation. The institution's image is an important factor in attracting public interest in the job training programs it organizes. This strategy allows BLK Surabaya to build closer relationships with the community, convey the institution's values, and highlight the excellence of its training services. Using a qualitative descriptive approach, this study identifies strategic efforts undertaken by BLK Surabaya, such as optimizing social media, utilizing alumni testimonials, strengthening its visual identity, and collaborating with digital communities. The results show that digital branding plays a significant role in increasing the institution's visibility, building public trust, and expanding the reach of training participants.